Pembelajaran Modern Matematika kepada anak Panti Asuhan melalui program GeMas (Gemar Matematika Dasar) - Dinda Salsabila; Randa Putra Sinaga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
The orphanage is a place where many children are placed because they don’t have a sense of belonging to the nuclear family. This sense of belonging triggers teenagers to be lazy to study, feel insecure to feel ashamed to learn something new. Adolescents who live in orphanages need a sense of belonging from their caregivers or their peers. However, this hope is difficult to achieve, this is due to conditions where the caregiver cannot fully become a parent. The number of caregivers is not balanced which causes the quality and quantity of support, attention, and affection from caregivers to be less than optimal. In addition, teenagers who live in orphanages come from different families, so they have differences both in cultural factors, habits, and socialization processes. So with that, the solution offered by the author is about how the children or teenagers were able to hone their critical and thorough thinking skills through learning mathematics. With the Casework method, the expected output on the mini project agenda that was offered was so that the children or youth at the orphanage were able to find their identity and capacity, especially in mathematics which has a strong connection with the education.